Oxford Handbook Topics in Psychology 2014
DOI: 10.1093/oxfordhb/9780199935291.013.001
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback for Sport and Performance Enhancement

Abstract: The technology of biofeedback has great promise for sport psychology and specifically for psychological skills training. Psychological skills learned through biofeedback training can be applied in practice and competition and can lead to improved athletic performance. This chapter includes a brief literature review of biofeedback and biofeedback training and describes the current state of biofeedback research in sport and its implications for athletic performance enhancement. Further, biofeedback training mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 6 publications
1
15
0
5
Order By: Relevance
“…The overall results of this study indicated that PE teachers in the LMA group exhibited the greatest improvement in reducing anxiety compared to the Games group. The results validated our basic hypothesis derived from previous research [7] and from applications of the LMA with elite athletes [7,9].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The overall results of this study indicated that PE teachers in the LMA group exhibited the greatest improvement in reducing anxiety compared to the Games group. The results validated our basic hypothesis derived from previous research [7] and from applications of the LMA with elite athletes [7,9].…”
Section: Discussionsupporting
confidence: 88%
“…The main feelings of anxiety experienced are worry, nervousness, and apprehension, which can contribute to a feeling of loss of control and depression in the long run, as well as a decrease in physical health [21,22]. Similar to the known interventions to reduce anxiety, such as physical activity, relaxation training, yoga and a variety of psychological interventions, the LMA approach can be used as an effective means to reduce and control physical education teachers' anxiety [7,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations